Regionalna polityka strukturalna Republiki Federalnej Niemiec (podstawowe koncepcje) - Dąbrowski, Adam (Wydział Prawa i Administracji UAM, 1994)
Basic elements of t h e regional structural policy in the Federal Republic of Germany are presented in the paper. The role of t he regional structural policy is first described in order to identify its objectives, scope, subjects, and instruments. The regional structural policy is a well-established component of the FRG's economic policy. A lederai state structure necessitates some specific regulations of the problem of relations between objects. The pyramid of objectives adopted within a social market economy defines the objectives of the regional structural policy. These objectives, in turn, determine appropriate instruments. Both theoretical and practical experience indicates that regardless of the extent of the state's economic interventionism, a regional structural policy must be continued.
The regional structural policy of the Federal Republics of Germany (basic concepts)